2016
DOI: 10.1186/s13039-016-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes in a genome-wise order: evidence for metaphase architecture

Abstract: BackgroundOne fundamental finding of the last decade is that, besides the primary DNA sequence information there are several epigenetic “information-layers” like DNA-and histone modifications, chromatin packaging and, last but not least, the position of genes in the nucleus.ResultsWe postulate that the functional genomic architecture is not restricted to the interphase of the cell cycle but can also be observed in the metaphase stage, when chromosomes are most condensed and microscopically visible. If so, it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…3 G ). The data are not only consistent with previous findings of haploid set separation in triploid cells (9, 42) but also with the parental origin model, in which each haploid set is spatially discrete and compartmentalized.…”
Section: Resultssupporting
confidence: 91%
“…3 G ). The data are not only consistent with previous findings of haploid set separation in triploid cells (9, 42) but also with the parental origin model, in which each haploid set is spatially discrete and compartmentalized.…”
Section: Resultssupporting
confidence: 91%
“…For example, are NHCCs formed between paternal–paternal, maternal–maternal, or paternal–maternal chromosomes? Or do they have a random combination, that is, based on a determined order of the genomic architecture (Nagele et al, 1995; Weise et al, 2016)? Addressing this question would require either a molecular or imaging technique that distinguishes between the contacts of parental alleles in an allele-specific manner.…”
Section: Watching Kissing Chromosomes In Real Time: Live-cell Imagingmentioning
confidence: 99%
“…Several studies were completed between 2002 and 2008, largely using FISH-banding to learn more about interphase and chromosome-structures. Studies based on FISH-banding in interphase confirmed that chromosomes principally keep their size and do not get extended like spaghetti during completion of the cell cycle [ 2 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. This finding remains in contradiction to most textbooks, which continue to incorrectly postulate that interphase chromosomes are completely decondensed.…”
Section: Contributions Of Prof Uwe Claussen To Human Cytogeneticsmentioning
confidence: 99%